A COMPREHENSIVE ANALYSIS OF THE DIGITAL INDIA SCHEME: CHALLENGES, OPPORTUNITIES AND FEATURES - Garg, Rajesh; Bindlish, Mohit; Kumar, Ramesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Digital India initiative is a key program of the Indian Government, launched on July 1, 2015. Its primary focus is the country’s digital development, aiming to provide citizens with access to services and facilities that connect them virtually and electronically. The program strives to bridge the gap between rural and urban areas by linking them through network devices and services. It is designed to ensure that even the poorest and most marginalized citizens can access government services electronically, thereby enhancing service delivery and improving the quality of life for all. To achieve this vision, efforts are being made to strengthen the country’s digital infrastructure, expand access to network devices with higher bandwidth, and implement advanced digital technologies. Additionally, initiatives are underway to increase digital literacy across the population, enabling more people to use digital tools and fostering job creation. To fully connect the nation, significant technological advancements are needed to propel India toward becoming a digitally empowered economy.